Efektivitas Instrumen Kebijakan Moneter Syariah dalam Menjaga Stabilitas Nilai Tukar - Serliani Lubis; Aufilana Rohmatika; Siti Aliyah; Rasidah Novita Sari (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Exchange rate stability is an important indicator in maintaining the balance of a country's economy, especially in facing global market dynamics. This research aims to analyze the effectiveness of sharia monetary policy instruments in maintaining exchange rate stability, with a focus on the principles of justice, transparency and stability which are the basis of the Islamic economic system. Instruments such as sukuk, mudarabah contracts, and ijarah are analyzed from theoretical and empirical perspectives to measure their impact on exchange rate fluctuations. This study uses a qualitative approach with analysis of secondary data obtained from various economic reports, scientific journals and related statistical data. The research results show that sharia monetary policy has significant potential in mitigating exchange rate volatility through stable liquidity management and a system free from speculation. Consistent implementation of sharia principles can also increase market confidence in the domestic currency. Furthermore, this research finds that integration between sharia monetary policy and conventional approaches can create synergy in maintaining exchange rate stability. This collaboration allows the monetary authority to be more flexible in responding to global economic challenges without abandoning sharia principles. Apart from that, educating market players regarding the benefits of sharia monetary policy is considered important to expand the adoption of this instrument. This study concludes that the successful implementation of sharia monetary policy is highly dependent on the commitment of the government and regulators in providing a conducive ecosystem, including financial infrastructure, strengthening regulations, and integrated policy support. This research provides theoretical and practical contributions in the development of sharia-based monetary policy in countries with dual economic systems.